A diaryl urea derivative, SMCl inhibits cell proliferation through the RAS/RAF/MEK/ERK pathway in hepatocellular carcinoma - Fu, Yue; Fang, Weiyue; Qiu, Fuqiang; Lai, Juncai; Xu, Yangjin; Chen, Bin; Li, Yang; Zhu, Xiaohui (Frontiers in Pharmacology, 2025)
IntroductionHepatocellular carcinoma (HCC) ranks among the three most prevalent cancer-related diseases in terms of incidence. Hence, exploring drugs for HCC therapy is of great significance. Compounds with a diaryl urea structure have been reported to exhibit a broad range of biological activities, including anticancer activity. This study focuses on the specific diaryl urea derivative 4-(4-(3-(2-chloro-3-(trifluoromethyl)phenyl)ureido)phenoxy)-N-methylpicolinamide (SMCl), with particular emphasis on investigating its therapeutic effects against hepatocellular carcinoma (HCC) and elucidating the underlying molecular mechanisms.MethodsIn vitro anti-cancer effects of SMCl were evaluated in HCC cell lines using MTS, colony formation, and wound healing assays. Western blot analyzed RAS/RAF/MEK/ERK pathway modulation. In vivo efficacy was assessed using a xenograft model.ResultsThe MTS and colony formation assays demonstrated that SMCl significantly decreased the viability of HCC cells. Western blot analysis demonstrated that SMCl effectively suppressed hepatocellular carcinoma proliferation by markedly inhibiting the RAS/RAF/MEK/ERK signaling pathway, with this inhibitory effect exhibiting both time- and concentration-dependent characteristics. SMCl also demonstrated significant therapeutic efficacy in the xenograft tumor model, achieving a tumor inhibition rate of 72.37%. Notably, it showed no significant impact on spleen weight or body weight in mice, indicating low toxicity to normal tissues.ConclusionThis study first elucidates the effects of SMCl on HCC cells and its impact on the RAS/RAF/MEK/ERK signaling pathway, providing a potential active compound for the clinical treatment of liver cancer.